ANALYSIS OF THE TEACHER'S ROLE IN ADDRESSING READINGDIFFICULTIES OF FIRST-GRADE STUDENTS AT PERHENTIAN LUASELEMENTARY SCHOOL - Chintia Amanda; Zaka Hadikusuma Ramadan (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
This paper indicates the problems that were conducted by direct survey in the research field. The difficulties in reading problems are found in the first-grade students in teaching and learning activities (KBM). It is intended to describe students’ reading difficulties and the teacher's role in overcoming reading difficulties for the first-grade students in one of the elementary schools in Perhentian Luas. The research method used in the research is a qualitative case study method. The location of the research was at SDN 001 Perhentian Luas. The sources of the research consisted of two teachers and eight first-grade students through observation, interviews, and documentation as data collection techniques. To test the data validity using triangulation and data analysis techniques by the Miles And Huberman model, data collection, data reduction, data presentation, and drawing conclusions were used. The research results come from there were eight first-grade elementary students who had difficulty reading. The types of difficulties experienced by students were lack of memory, difficulty in spelling, difficulty in pronouncing letters, errors in substituting letters, and less familiarity with letters. The teacher's role in overcoming reading difficulties for grade I elementary students as an educator is to remind, train, assist, and assist in directing students and guiding students in the learning process. As a motivator, teachers motivate students to make students more confident in class. As a facilitator, teachers provide interesting and effective lesson plans as well as media to attract students' attention while studying. As a demonstrator, teachers master science and knowledge first, then convey it by applying teaching and learning methodslike the spelling method while learning reading. And lastly, as an evaluator, teachers provide an evaluation and follow-up learning activity for students when the activity is over.